Naphthaldehyde-based Schiff base dyes: aggregation-induced emission and high-contrast reversible mechanochromic luminescence. (25th July 2022) - Shen, Lingyi; Yu, Chang-Jin; Xie, Hai-Fang; Xu, Na; Xu, Hong; Huang, Ya-Li; Redshaw, Carl; Feng, Xing; Zhang, Qi-Long
Abstract : This work provides a naphthaldehyde-based Schiff base with reversible multiple stimuli-responsive behaviour of AIEE mechanochromic luminescence, which functions as a sensitive chemosensor for Cu 2+ ions. Abstract : Mechanochromic luminescent materials have attracted intense attention because of their excellent reversible optical behaviour, but the mechanism of the stimuli responsive behaviour remains ambiguous. Herein, a novel naphthaldehyde-based Schiff base, namely N 2, N 6 -bis(2-(2-hydroxynaphthalen-1-yl)phenyl)pyridine-2, 6-dicarboxamide (HNP ) exhibiting both aggregation enhanced emission (AIEE) and excited state intramolecular proton transfer (ESIPT) characteristics has been synthesized. The mechanism of the reversible mechanochromism was investigated via experimental and theoretical procedures. Crystalline HNP exhibits a reversible mechanochromism from yellow to orange emission under external stimulus and back to yellow emission by fuming under a dichloromethane atmosphere. Single crystal X-ray diffraction analysis indicated that the compound HNP adopts two types of molecular conformations with different intramolecular torsion angles. Meanwhile, DFT and TD-DFT calculations demonstrated that the torsion angle change directly affects the electronic distribution, resulting in a discriminable energy gap. Clearly, the different molecular conformations play a crucial role in triggering the reversible mechanochromism upon grinding. Additionally, HNP is an excellent fluorescent probe for detecting Cu(ii ) ions in solution. Thus, this example not only provides clear evidence to clarify the mechanism of reversible mechanochromism, but also offers a new on-off chemosensor for Cu(ii ) ion detection.